Critical Historical Criminology in the Antipodean: Unthinking History and Criminology in the Global South - Roberto Catello (International Journal for Crime, Justice and Social Democracy, 2023)
This paper makes a call for a critical historical criminology of the antipodean and the Global South. It makes a preliminary argument for a critical historical criminology that is against method and in favour of political alliances with critical perspectives that can enrich historico‑criminological understandings in an antipodean and Southern context. In particular, this paper explores the potential for a politico-academic alliance between critical historical criminology and postcolonial studies, Southern theory and Indigenous research. Such politico-academic alliances reveal that critical historical criminology is best understood as a negation of both criminology and history and that historical criminology does not have to be understood as a new sub-discipline and academic specialism at the intersection of history and criminology. On the contrary, this paper argues that historical criminology can be approached as a critical attempt to ‘unthink the social sciences’ and to ‘de-discipline ourselves’.